Could workplace accidents covered by social insurance workers compensation funds be used to calculate national indicators for surveillance of occupational injuries in France?. (1st March 2011) - Brière, J; Chevalier, A; Feurprier, M; Paboeuf, F; Imbernon, E
Abstract : Background: Financial compensation for workplace accidents are paid by several funds in France. The advantage of these data is that each fund determines if the accident was work-related. But funds function independently and there have no efforts to make the data consistent or to centralise them. Another disadvantage is related to the kind of data, which is recorded for administrative purposes and not for epidemiologic surveillance. Methods: The French Institute for Public Health Surveillance used individual information of occupational injuries of the three principal funds (84% of employees) for the year 2004. We defined essential information (especially the victim's sex and age, economic sector, occupation and cause of accident) and matched nomenclatures. We calculated national indicators for each fund and for all the funds: the number of occupational injuries, the incidence rate of cases of occupational injury, the proportion of serious and fatal injuries (according sex, age, economic sector). Results: The number of occupational injuries for the three funds was 914 803 for men, 370 053 for women. The incidence rate reached 8.8 (per 100 employees) for men, 4.6 for women. The three leading sectors were construction (14.3), transport (10.9) and agriculture and food processing industry (10.4) for men, agriculture and food processing industry (7.0), education health and social action (6.8) and services to individuals (6.4) for women. Conclusions: Calculation of national indicators for surveillance of occupational injuries seems possible. Recommendations will be proposed for the purpose of improving surveillance.